Identification of heat tolerant barley genotypes based on heat susceptibility index - Devi, Suman; Kumar, Yogender; Shehrawat, Sachin (Journal of Cereal Research, 2021)
The present experiment was planned to understand the impact of high temperature on grain yield and its component traits in order to select heat tolerant genotypes for future breeding programmes. Fifty barley genotypes were evaluated under two environments created by different dates of sowing i.e. timely sown and late sown, during Rabi 2016-17. The mean sum of squares due to genotypes based on heat susceptibility index (HSI) revealed the presence of significant variation for all the traits except plant height, spike length and grains per spike. Correlation among HSI of different traits indicated significant positive association of grain yield per plot with harvest index, biological yield, 1000-grain weight, plant height and days to maturity. Out of 50 genotypes studied, HUB 242 exhibited lowest HSI and percent reduction in grain yield under heat stress conditions. The genotypes namely HUB 242, DWRUB 52, RD 2904, BH 902 and IBYTHI- 13 were found most promising based on heat susceptibility index (HSI) of grain yield. However, based on overall rank of HSI of all the traits, IBON-HI-13, IBYT-HI-13, RD 2904, HUB 242 and IBON-HI-3 were identified heat tolerant genotypes. These genotypes could be utilized as promising breeding material for the development of new heat tolerant barley varieties.